Development and advancement of thin CdTe-based solar cells for photovoltaic performance improvements - Bothwell, Alexandra, author; Sites, James, advisor; Krueger, David, committee member; Gelfand, Martin, committee member; Sampath, Walajabad, committee member; Topič, Marko, committee member (Colorado State University. Libraries, 2020)
Photovoltaic technologies, with an essentially infinite energy source, large total capacity, and demonstrated cost competitiveness, are well-positioned to meet growing global demand for clean energy. Cadmium-telluride (CdTe) thin-film photovoltaics is advantageous primarily for its direct optical band gap (approximately 1.48 eV) which is well-matched to the standard AM 1.5G solar spectrum, and its high absorption coefficient. These advantages, in tandem with innovations in fabrication and photovoltaic design in the past decade, have significantly increased CdTe photovoltaic device performance and reduced cost. Major advances in CdTe device performance have been achieved through improved current collection and fill factor, however, the open-circuit voltage (VOC) of CdTe devices remains limited compared to the band gap-determined maximum achievable VOC. The voltage deficit could be minimized through various approaches, and this work addresses it through progressive structural changes to a thin CdTe device. Absorbers of less than 2 µm were pursued for ultimate electron-reflector devices which incorporate a wide band-gap material behind the absorber to induce a back-surface field via a back-side conduction-band offset for improved VOC. An optimized and stable base structure is necessary to quantify characteristics and improvements in progressive devices with additional material layers. Thin, 0.4-1.2 µm CdTe absorber devices were optimized and demonstrated respectable and repeatable performance parameters, and a maximum efficiency of 15.0% was achieved with only 1.2 µm CdTe. Capacitance measurements also showed that thinner devices had fully-depleted absorbers into forward bias. To improve device performance through increased current collection, a 1.4-eV band gap CdSeTe layer was introduced as an additional absorber material preceding CdTe. Prior understanding of the effects of the additional CdSeTe material was incomplete, and this work deepens and expands this understanding. Performance improvement was achieved for thin, 1.5-µm absorber devices with no intentional interdiffusion of the CdSeTe and CdTe. The importance of the CdSeTe thickness was demonstrated, where performance was consistently reduced for CdSeTe thickness greater than CdTe thickness, independent of CdSe composition in the close-space sublimation (CSS) CdSeTe source material. Longer time-resolved photoluminescence (TRPL) tail lifetimes in CdSeTe/CdTe devices compared to CdTe devices suggested better bulk properties, and current loss analysis showed that CdSeTe is the dominant absorber in 0.5-µm CdSeTe/1.0-µm devices. 1.5-µm CdSeTe/CdTe devices demonstrated increased current collection and 30-mV voltage deficit reduction due to the 100-meV narrower band gap of CdSeTe compared to CdTe and passivating effects of selenium, for an ultimate efficiency improvement to 15.6%. Lattice-constant matching to CdTe and wide, ~1.8-eV band-gap requirements directed the selection of CdMgTe as the electron-reflector layer. CdMgTe was incorporated into the CdSeTe/CdTe device structure first through CSS, but sputter deposition was found to be more favorable to address the material complexities of CdMgTe (temperature-induced magnesium diffusion and CdCl2 passivation loss, doping, and MgO formation), and produced higher performing CdMgTe electron-reflector devices. Low substrate temperature achievable in sputtered CdMgTe deposition proved the greatest advantage over CSS-CdMgTe: CdCl2 passivation and magnesium can be appropriately maintained with a corresponding maintenance of device performance, whereas temperature-induced CdCl2 passivation loss or magnesium loss will occur for CSS-deposited CdMgTe with incumbent performance reduction. Through low-temperature depositions, doping optimization, and small structural adjustments, 16.0% efficiency was achieved with CdMgTe sputtered on 0.5-µm CdSeTe/1.0-µm CdTe absorbers, the highest-known CdMgTe electron-reflector device performance. The CdMgTe and non-CdMgTe-containing device VOC's suggested that electron reflection was enacted with partial success for the sputter CdMgTe-incorporated structure, but the significant improvements expected based on simulation have not been realized due to MgO formation and a negative valence-band offset which somewhat impedes hole transport to the back contact. Suggestions to overcome or circumvent these limitations are presented and discussed in the context of progressed understanding of CdMgTe electron-reflector devices.
Keywords: electron reflector; solar energy; CdTe; thin film; photovoltaics